Elaboración de un simulador con geogebra para la enseñanza de la fisica. El caso de la ley de coulomb - SÁNCHEZ SÁNCHEZ, Ivonne Coromoto (Universidade Federal de Mato Grosso, 2022)
With the arrival of the 21st century, the use of digital technologies in the teaching of Mathematics and Natural Sciences is more noticeable. One of the most used types of resources is computer simulators. Research focused on the implications of the use of these digital resources in teaching little comment on the potential of the development of simulators for learning, much less the mathematics that emerges in this activity. Based on this consideration, this work describes the sequence of simulation tasks solved with GeoGebra that allow one to emulate one of the electrostatic phenomena of attraction and repulsion, linked to Coulomb's Law. The description includes the specification of the emerging mathematical content in the activity, as well as a subjective assessment of the potential of GeoGebra for learning physical phenomena and the emerging mathematical content of the experience.